Kinetic Studies of Reduction of Tris-(1,1,1,5,5,5-hexafluoroacetylacetonato) ruthenium(III) in Methanol, Ethanol and Propanol - Ezekiel Dixon Dikio (E-Journal of Chemistry)
The complex tris-(1,1,1,5,5,5-hexafluoroacetylacetonato-) ruthenium(III), hereafter referred to as Ru(hfacac)3, has been synthesized. Ultraviolet and visible spectroscopic measurements of the complex in ethanol revealed three prominent absorption bands at 287, 374 and 525 nm with molar absorptivity coefficients of 4.113, 3.885 and 3.59 respectively. Magnetic susceptibility measurements between 78 and 296 K revealed the complex to assume a low spin configuration of e0 t2g5 and an oxidation state of +3 as inferred from a value of 1.92 Bohr magneton. Kinetic investigation of the reduction of the complex in methanol, ethanol and propanol indicate the reduction to proceed in the order methanol > ethanol > propanol. The energies of activation of the reduction in methanol and ethanol were found to be 85.4 and 108 kJ/mol respectively.